The Influence of Social Media Marketing on Consumer Brand Engagement (Adidas Study on Tiktok Application in Bandung City) - Abi Nubli Adzhani; Teguh Widodo (Quantitative Economics and Management Studies, 2023)
In the rapidly developing digital era, social media, especially TikTok, has become an important platform for brand marketing. Adidas, as a leading global brand, uses TikTok to increase interaction with consumers, especially in the city of Bandung. However, it still needs to be understood to what extent Social Media Marketing on TikTok influences consumer engagement with the Adidas brand. This research aims to explore this, providing important insights for marketing strategies in this digital era. This research explores the impact of Social Media Marketing on consumer engagement with brands, especially on the TikTok application, with a focus on the Adidas account in Bandung City. This research used 417 samples collected through an online questionnaire with a purposive sampling technique with the criteria of being 17 - 25 years old, active social media users who follow the Adidas account on TikTok. The results of the analysis show that the Consumer–brand engagement variable has a significant effect on the Brand Awareness variable, the Consumer Brand Engagement variable has a significant effect on the Brand Image variable, the Customization variable has a significant effect on the Consumer Brand Engagement variable, the E-Wom variable has a significant effect on the Consumer Brand Engagement variable, the Entertainment variable has a significant effect on the Consumer variable, the Brand Engagement variable, the Interaction variable has a significant effect on the Consumer Brand Engagement variable, the Trendiness variable has no significant effect on Consumer Brand Engagement. This research provides important insights for companies like Adidas in designing more effective social media marketing strategies.